Antimicrobial Resistance in Vibrio cholerae from Aquatic Environment - Reethy, P. S.; Lalitha, K. V. (Fishery Technology, 2021)
Vibrio cholerae is an enteric pathogen causing an acute diarrheal disease known as cholera. The disease is acquired through the consumption of food or water contaminated by this microorganism. Antibiotic therapy is recommended in specific situations to significantly reduce the volume of watery faeces and duration of diarrhoea, reducing the transmission of infection. The wide use and abuse of antibiotics in human and veterinary medicine, agriculture, and aquaculture systems have caused the emergence of antimicrobial resistance (AMR) in V. cholerae. Several epidemics worldwide were caused by multidrug-resistant (MDR) V. cholerae. Various resistance patterns are reported among clinical strains isolated from different parts of the country and across the globe. The drugresistant clinical strains are dispersed into the aquatic environment through faeces/ excreta of humans, discharge from health care facilities or contaminated groundwater. In the aquatic environment, V. cholerae that are susceptible to antibiotics acquire resistance either by frequent exposure to antibiotics over a period of time or through the transfer of resistant genes from other resistant bacteria. In the aquatic system, genetic exchange between bacteria is readily facilitated resulting in the higher frequency of AMR V. cholerae and more commonly exhibited multiple antibiotic resistance.